Strategi Optimalisasi Sistem Pembinaan Penyidik Polri Guna Meningkatkan Kinerja Organisasi - Dadang Hartanto (Universitas Negeri Medan, 2020)
In an effort to optimize organizational performance, various strategies are needed, especially in the police field of investigation. Various efforts can be made in the form of implementing a reward system, a certification system and a performance appraisal system. But until now it is still partial and has not provided a sense of justice and increased motivation. Merit system has not become a foundation in the system. This is influenced by several main factors, namely the role of leadership, mental models of Criminal Investigation personnel, surveillance systems. Stakeholder support is still limited to discourse and in the operational field. Stakeholders in the budget sector are still oriented to other fields of activity outside of coaching. The use of information technology that is still partial does not support the operation of the investigator guidance system. Operationalisation of the system that is still manual also still occurs so that the data and information collected cannot be optimally processed in determining the performance displayed by the National Police investigator, the rewards given as well as the competency map and special areas of expertise. These factors are influenced by mental models in definitive routines, the attention of leaders and blueprints for the design of an IT-based police investigating system. Therefore, the mental model that encourages innovation and breakthrough needs to be created, the struggle of leaders in setting programs and budgets as well as the blueprint for system design that is complete and ready to be followed up.